2017
DOI: 10.11648/j.ijbbmb.20170206.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotype and Hen Age on the Egg Shape Index

Abstract: Shape index was a good indicator to characterize species as well as for egg quality. It seems that shape index affected by genetic and environment factors. In this study, the aim was to determine the influence of genotype and age on the shape index. A total of 789 eggs were collected from four genetic lines (Black, Black with brown neck, White Shank feather and White non-Feathering shank) of the Kurdish Chickens when the hens 52 -65 week-old. Results indicated that significant differences were observed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Eggs can be classified according to their shape into long, normal, and round. Long eggs have a shape index less than 72, normal eggs between 72 and 76, and round eggs greater than 76 [41]. The present study found uniformly normal oval eggs with a mean shape index between 75% and 76%.…”
Section: Temperature (supporting
confidence: 54%
“…Eggs can be classified according to their shape into long, normal, and round. Long eggs have a shape index less than 72, normal eggs between 72 and 76, and round eggs greater than 76 [41]. The present study found uniformly normal oval eggs with a mean shape index between 75% and 76%.…”
Section: Temperature (supporting
confidence: 54%
“…The similar yolk color found, in all eggs might indicate that there was not much change in the carotenoid content of the experimental diets due to the supplementation of SRFPKC. Since the egg shape index is influenced not by the diets but by genotype (Shaker et al, 2017), age of hens, and ambient temperature (Nikolova and Kocevski, 2006), it is expected that the effect of supplementation of SRFPKC in the diet on egg shape index is statistically undetected in this present study. This finding is in accordance with the study of Liu et al (2020).…”
Section: Resultsmentioning
confidence: 72%
“…Hal ini menunjukkan bahwa kandang sistem pemeliharaan tidak mempengaruhi indeks telur ayam Ketarras. Shaker et al (2017) menyatakan bahwa indeks telur dipengaruhi oleh genetik. Indeks telur ayam Ketarras ini tidak berbeda dengan indeks telur ayam petelur.…”
Section: Indeks Telurunclassified